Synthesis and Characterization of New Symmetrical Pyromellitdiimide Derivatives and Their Amic Acids - Ali, E. T.; AL-Aliawy, K. M. Lazim; Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The new symmetry pyromellitdiimide [VII]a-c,n were synthesized by two-step reactions from the corresponding pyromellitic dianhydride . A new symmetrical amic acid [VI]a-c,n was synthesized by the reaction of pyromellitic dianhydride with different heterocyclic amines in dry acetone . The second reaction step includes intramolecular cyclization of amic acid in the presence of sodium acetate -acetic anhydride system at 850C. Structures of the synthesized compounds have been ascertained by their melting points , C.H.N analysis , UV-Vis, FTIR and 1HNMR spectroscopy.